2019
DOI: 10.1177/2474126419856464
|View full text |Cite
|
Sign up to set email alerts
|

Educational Impact of a Podcast Covering Vitreoretinal Topics: 1-Year Survey Results

Abstract: Purpose: This article aims to determine preferences and demographics for listeners of an ophthalmology podcast, since podcasts are gaining favor for medical education. Methods: The present study used a cross-sectional, online survey as well as Podtrac, Inc and Squarespace, Inc platform analytics to examine perceived educational usefulness of podcasts for listeners. Results: Quarterly episode downloads increased from 684 in first-quarter 2017 to 16 016 in third-quarter 2018. A total of 102 participants complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
5
0
4
Order By: Relevance
“…Numerous articles in the current literature have demonstrated the benefits of podcasts in all levels of medical education and across various subspecialties 7,22-24 . Pertaining to the field of orthopaedics, Back et al demonstrated that medical students obtained a greater amount of knowledge and satisfaction from their orthopaedic curriculum when utilizing podcasts than when using traditional textbooks for learning 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles in the current literature have demonstrated the benefits of podcasts in all levels of medical education and across various subspecialties 7,22-24 . Pertaining to the field of orthopaedics, Back et al demonstrated that medical students obtained a greater amount of knowledge and satisfaction from their orthopaedic curriculum when utilizing podcasts than when using traditional textbooks for learning 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai penelitian terdahulu menunjukan siniar efektif sebagai sarana belajar. Sifat siniar yang terdistribus (Venincasa et al, 2019) dan mampu didengarkan melalui personal komputer dan media portable seperti telepon pintar (Taylor et al, 2012), memungkinkan siniar didengarkan tanpa bantasan ruang dan waktu. Penelitian Venincasa et al (2019) menemukan bahwa episode siniar yang lebih dari setahun setelah rilis masih terus diakses.…”
Section: Penggunaan Siniar Untuk Pendidikanunclassified
“…Sifat siniar yang terdistribus (Venincasa et al, 2019) dan mampu didengarkan melalui personal komputer dan media portable seperti telepon pintar (Taylor et al, 2012), memungkinkan siniar didengarkan tanpa bantasan ruang dan waktu. Penelitian Venincasa et al (2019) menemukan bahwa episode siniar yang lebih dari setahun setelah rilis masih terus diakses. Hal ini menunjukan bahwa siniar memiliki ketersediaan longitudinal yang berharga untuk kelompok pelajar yang terus tumbuh.…”
Section: Penggunaan Siniar Untuk Pendidikanunclassified
See 2 more Smart Citations